Professional Training of Future Doctors Using Cloud Technologies - Yefremova, Oksana; Humeniuk, Mariia; Salyzhyn, Tetiana; Humeniuk, Vasyl; Korniichuk, Oleksandr (Cadernos de Educação Tecnologia e Sociedade, 2024)
The conducted study aimed for the integration of cloud technologies into the educational process to evaluate their influence on different aspects of the professional competence of future doctors. For this, methods of comparative analysis, questionnaire, expert assessment, observation and statistical analysis were used. Results showed that students of the experimental group demonstrated significant improvement in the professional competence of such components as cognitive, motivational-volitional and organizational performance aspects. This confirms the importance of the skill to effectively use digital technologies in both professional and personal life spheres. The use of cloud technologies such as Google Docs, Pbwiki, Sway, Microsoft Azure, and Microsoft Planner led to significant improvements in students’ results. Still, at the beginning, many teachers doubted these tools, although their attitude changed with time. Thus, reconsideration of educational programs to ensure their compliance with world education standards, in particular through the integration of new technologies, contributing to the development of professional competencies is relevant. The scientific novelty of the research is stipulated by the insufficient number of studies devoted to the use of cloud technologies in training future doctors.